Pre-Hospital Paediatric Life Support : the Practical Approach. - Group, Advanced Life Support (John Wiley & Sons, 2007)
This practical book written especially for prehospital staff provides all the information needed to deal with children in life threatening situations before arriving at hospital. It is a complementary volume to the best-selling Advanced Paediatric Life Support.